Targeting brain‐derived neurotrophic factor in the treatment of neurodegenerative diseases: A review - Dong Wang; Zhi‐Chen Lang; Shi‐Nan Wei; Wei Wang; Hao Zhang (Neuroprotection)
Abstract Neurodegenerative diseases, marked by the gradual death of neurons, present a significant and growing public health challenge. Brain‐derived neurotrophic factor (BDNF) is crucial for the survival, development, and synaptic plasticity of neurons. Studies have consistently demonstrated that perturbed BDNF communication pathways are associated with the development and progression of neurodegenerative conditions, underscoring their potential as therapeutic targets. This review aimed to summarize the existing findings regarding BDNF expression, metabolism, and signaling transduction. Furthermore, we reviewed the intricate roles of BDNF signaling pathways in neurodegenerative diseases, elucidating their contributions to disease onset and progression. The latest advancements in targeting BDNF for the treatment of neurodegenerative diseases, including the development of small molecules, nucleic acid‐based therapeutics, and antibody‐based approaches, were also summarized. Despite recent strides, challenges persist, including a lack of comprehensive understanding of BDNF modulation across diverse neurodegenerative contexts and the absence of clinically approved BDNF‐targeted drugs.